2022
DOI: 10.3390/en15134600
|View full text |Cite
|
Sign up to set email alerts
|

Purchase Behavior of Energy-Efficient Appliances Contribute to Sustainable Energy Consumption in Developing Country: Moral Norms Extension of the Theory of Planned Behavior

Abstract: Since energy consumption in developing countries has increased significantly, motivating energy-saving habits among citizens is an important issue both from the academic and industrial perspectives. Thus, this study aims to predict consumer purchase intention for energy-efficient household appliances based on an extended model of the Theory of Planned Behavior (TPB). This study incorporated two additional constructs of moral norms and environmental concern in the model of the TPB. A self-administered questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 99 publications
0
7
1
Order By: Relevance
“…Regarding the significance of subjective norms toward PEBI, our findings contradict earlier studies (Çoker and van der Linden, 2022; Hossain et al , 2022). One possible explanation for the insignificance of the norms effect is that consumers lack knowledge (Pendry et al , 2012) to inform and share with others about non-DBD options.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Regarding the significance of subjective norms toward PEBI, our findings contradict earlier studies (Çoker and van der Linden, 2022; Hossain et al , 2022). One possible explanation for the insignificance of the norms effect is that consumers lack knowledge (Pendry et al , 2012) to inform and share with others about non-DBD options.…”
Section: Discussioncontrasting
confidence: 96%
“…In addition to motivation, subjective norms are a significant element in the prediction of PEBI (Hossain et al , 2022). This term refers to the perspective of others that is regarded as relevant to an individual, whose decisions are influenced by these opinions (Ajzen, 1991).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Multiple studies on conservation behaviors have accordingly recently applied the TPB in both organizational and domestic settings [ 37 ]. In most studies, subjective norm has been found to be the parameter that mostly affects intention to act pro-environmentally [ 38 , 40 ] and to conserve energy [ 54 ] in the TPB model. However, in other studies subjective norm had no direct effect on pro-environmental behavioral intentions [ 41 ].…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%
“…However, in other studies subjective norm had no direct effect on pro-environmental behavioral intentions [ 41 ]. Attitude and perceived behavioral control has had a direct influence on pro-environmental behavioral intentions which encourage active engagement in pro-environmental behaviors [ 40 , 41 ]. Perceived behavioral control has also had a significant effect on energy conservation intentions of students with physical impairments but not a direct effect on their behaviors, while attitude had the lowest power to predict intentions to perform energy-saving behaviors [ 54 ].…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation